ANALISIS POSISI DETEKTOR TERHADAP STEM EFFECT DAN DOSIS RELATIF UNTUK DOSIMETRI PESAWAT LINAC 6 MV - Nurul Laili Khoirut Tabi’atin; Evi Setiawati; Zaenal Arifin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Research conducted aims to determine the effective position’s detector for Percentage Depth Dose ( PDD ), crossline and inline scanning in dosimetry linac 6 MV with analisys of relative dose and minimal stem effect on the detector. Research carried out by using detector CC TNC / 9770 and detector CC TNC / 9776 with variety on the position of the detector on axes x1, y1, x2 and y2, and wide field irradiation of 10 x 10 cm2 at SSD 100 cm. On this research for PDD scanning, position’s detector coincide to relative dose and at any depth. The largest is in position y1 with measurement dose 100.06 %. So position y1 used as reference position for measurement of stem effect. For PDD scanning ratio stem effect on the position of y2, x2, and x1 are 0.260521 %, 0.049995 % and 0.140112 %. So the effective position’s detector for PDD scanning is position x2 with the ratio of the smallest stem effects is 0.049995 %. For crossline scanning, position x1 used to an form position for measurement of stem effect because have the largest measurement of relative dose that is 100.04 %. For crossline scanning ratio stem effect on the position of y1, x2 and y2 are 0.080032 %, 0.080032 % dan 0.240481 %. In position y1 and x2 have a same of ratio stem effect, but based on distribution of measurement dose in the beginning and the end scanning, effective position of the detector for crossline scanning in position y1. For inline scanning, position x1 used as reference position for measurement of stem effect because have the largest measurement of relative dose that is 100.00 %. So position y1 used as reference position for measurement of stem effect. For inline scanning ratio stem effect on the position of y2, x2, and x1 are 0.070049 %, 0.020004 % and 0.010001 %. So the effective position’s detector for inline scanning is in position x1 which has the smallest stem effect is 0.010001 %.Keyword: PDD scanning, crossline scanning, inline scanning, relative dose, stem effect.